Cement with bacterial nanocellulose cured at reservoir temperature: Mechanical performance in the context of CO2 geological storage - Barría, Juan Cruz (2021)
Storing CO2 in deep underground reservoirs is key to reducing emissions to the atmosphere and standing against climate change. However, the risk of CO2 leakage from geological reservoirs to other rock formations requires a careful long-term analysis of the system. Mostly, oil well cement used for the operation must withstand the carbonation process that changes its poromechanical behavior over time, possibly affecting the system’s integrity. This work focuses on the microstructure and mechanical behavior of cement modified with bacterial nanocellulose (BNC) cured at 90 ◦C, simulating temperature at the reservoir level. The chemohydro-mechanical (CHM) coupled behavior of the cement–rock interface is also investigated through numerical analyses. Mercury intrusion porosimetry (MIP), X-ray diffraction (XRD), ultrasonic wave velocity measurement, and unconfined compressive strength (UCS) tests were performed on cement samples subjected to a supercritical CO2 environment. After carbonation, BNC samples show a lower mass gain and lower porosity compared to PC. Permeability based on MIP results indicate that the BNC reduces the permeability of the specimen. XRD quantification shows no substantial difference between the crystalline phases of the two samples. Samples with BNC have lower absolute strength but higher relative increase during carbonation. The numerical study includes a homogenization of the medium considering the contribution of all components. CHM behavior of the cement with BNC is analyzed, and the results show the variations of the physical and chemical properties across the sample. The numerical study shows the advantage of using this type of tool to study realistic CO2 injection scenarios in deep wells.